The Prosocial class: how social class influences prosocial behavior - Vieites, Yan Bernardes (2017)
The concept of noblesse oblige establishes that the diﬀerential in privileges between the rich and the poor should be balanced by a diﬀerential in duties towards those in need. However, the empirical ﬁndings regarding which are the most prosocial groups havebeenascontroversialasthisassertive. Whereasresearchintheso-calledpsychological framework has advocated a negative relationship between social class and prosocial behavior, the economic approach has claimed the opposite (i.e., positive) direction to be true. This article sought to disentangle conﬂicting ﬁndings from these strands of research across two diﬀerent studies. In the ﬁrst study, we conducted a series of focus groups in both wealthy and impoverished areas. Results suggested that research in the domain of social class has been circumscribed to an almost conventionalized few prosocial behaviors that are not representative neither of wealthy nor of poor individuals. In the second study, we conducted surveys in the same areas. Results revealed that, despite having less resources and opportunities to help others, lower social class individuals are more prosocial than their upper-class counterparts. Furthermore, prosociality diﬀerences cannot be explained by a diﬀerent pattern of targets of help across the social spectrum. Implications for practice and research on prosociality are also discussed.